INDIVIDUAL LEGAL REGULATION IN THE CONTEXT OF LEGAL REFORM - Шапенко, Людмила Олександрівна; Мельничук, Ірина Степанівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2020)
Purpose: the purpose of the article is to determine the content of the concept of individual legal regulation in the context of current trends in the legal system of Ukraine, as well as its role and importance in the mechanism of legal regulation. Methods: the methodological basis of the study are general scientific and special legal methods of cognition, which studied scientific approaches and doctrinal positions of understanding individual legal regulation, in particular the essence of its socio-managerial nature of functioning. The results of scientific research allow us to interpret individual legal regulation as the authoritative activity of competent entities, which involves making additional decisions on the organization of public relations on the basis of current legislation by specifying the scale of behavior of their personal participants. Also, the initial principle of the proposed scientific work is the development of theoretical provisions that determine the features of individual legal regulation associated with the action of a mechanism that combines all legal means and with the help of individual orders regulates certain casual social relations. Discussion: in the current conditions of transformation of public relations and implementation of legal reform in Ukraine, individual legal regulation is becoming increasingly important, which is to ensure the solution of specific legal situations and meet the needs and interests of specific actors. And this, in turn, highlights the need for constant solution of scientific problems related to individual legal regulation, which will undoubtedly become a theoretical value for the entire legal system, and in terms of practical significance of the study, will be a set of proposals to improve the current legislation of Ukraine, as well as recommendations for improving the practice of its implementation.